The role of west java National Amanat Party (PAN) organizational communications in educating communities persuasive communications during the Covid-19 Pandemic - Azmi Abi Faris; Yoseph Mahdi Yunansyah (Gema Wiralodra, 2023)
The objective study is how the party mandates national West Java to educate people persuasively during the Covid-19 pandemic. The research method that will be used in this research is descriptive qualitative. This research uses source data primary and secondary. The researcher also did interviews and observations to obtain preliminary data regarding persuasive community education during the COVID-19 pandemic. Based on observation And observation as well analysis done researcher, so results from the study of This role of communications organization done by the Board Leader Region Java West (DPW) are Already very Good from the regional level to the level of the Leadership Council of the West Java National Mandate Party Branch. DPW Pan West Java plays on its intentions by conducting persuasive communication in educating the public about the 5M campaign, namely keeping their distance, washing hands, using a mask, staying away from crowds, and limiting mobilization and interactions. The conclusion from this study is that the role of organizational communication carried out by the DPW PAN of West Java is very optimal and structural in providing information, socialization, and education-related campaign 5M to the public in a persuasive manner. Matter this can look at the progress done by the Board Leader Region West Java to its members intensely through various routine discussion forums, which are also carried out through discussion forums through the internal WhatsApp group of the West Java PAN Regional Leadership Council.